Personal Protectice Equipment Reference Guide for Low-Volume Citrus Applicators - Stephen H. Futch; Lukasz L. Stelinski; Lauren M. Diepenbrock; Jamie D. Burrow (EDIS, 2018)
This 2-page fact sheet is a minor revision written by S. H. Futch, L. L. Stelinski, L. M. Diepenbrock, and J. D. Burrow, and published by the Horticultural Sciences Department, August 2018.